2021
DOI: 10.1155/2021/7665169
|View full text |Cite
|
Sign up to set email alerts
|

Tackling of Renal Carcinogenesis in Wistar Rats by Silybum marianum Total Extract, Silymarin, and Silibinin via Modulation of Oxidative Stress, Apoptosis, Nrf2, PPARγ, NF‐κB, and PI3K/Akt Signaling Pathways

Abstract: The present work was designed to assess the efficacy of Silybum marianum total extract (STE), silymarin (Sm), and silibinin (Sb) against experimentally induced renal carcinogenesis in male Wistar rats and their roles in regulating oxidative stress, inflammation, apoptosis, and carcinogenesis. The diethylnitrosamine (DEN)/2-acetylaminofluorene (AAF)/carbon tetrachloride (CCl4)-administered rats were orally treated with STE (200 mg/kg b.w.), Sm (150 mg/kg b.w.), and Sb (5 mg/kg b.w.) every other day either from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 101 publications
1
11
0
Order By: Relevance
“…To explore the mechanism of silibinin inhibiting oxidative stress, we tested Nrf2, a key factor regulating oxidative stress homeostasis, and ADH3 and ALDH2, two key enzymes regulating formaldehyde metabolism. In the literature related, silibinin activated Nrf2 signaling to modulated oxidative stress [ 64 , 65 ], and we showed similar results that silibinin increased Nrf2 nuclear translocation and transcription of downstream genes in FA-treated mice. Moreover, Nrf2 regulates the ALDH2 expression, and interestingly, ALDH2 can increase the Nrf2 expression, suggesting an NRF2-ALDH2 feedback loop [ 66 68 ].…”
Section: Discussionsupporting
confidence: 82%
“…To explore the mechanism of silibinin inhibiting oxidative stress, we tested Nrf2, a key factor regulating oxidative stress homeostasis, and ADH3 and ALDH2, two key enzymes regulating formaldehyde metabolism. In the literature related, silibinin activated Nrf2 signaling to modulated oxidative stress [ 64 , 65 ], and we showed similar results that silibinin increased Nrf2 nuclear translocation and transcription of downstream genes in FA-treated mice. Moreover, Nrf2 regulates the ALDH2 expression, and interestingly, ALDH2 can increase the Nrf2 expression, suggesting an NRF2-ALDH2 feedback loop [ 66 68 ].…”
Section: Discussionsupporting
confidence: 82%
“…43 In various studies conducted, it was reported that silibinin was effective in treating arsenic-induced nephrotoxicity by eliminating oxidative stress, inflammation, and apoptosis in rats, and that silibinin also activated GST enzyme activity. 44 In the study conducted by Yassin et al (2021), in which they examined the effectiveness of silymarin and silibinin against experimentally induced renal carcinogenesis in male Wistar rats, it was reported that silymarin and silibinin application weakened toxicity indicators in serum, decreased lipid peroxidation, considerably strengthened renal antioxidant arsenal, as well as increased GST enzyme activity and decreased GR enzyme activity. 45 In vitro experiments showed that silibinin nanoparticles protect liver cells and reduce cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…44 In the study conducted by Yassin et al (2021), in which they examined the effectiveness of silymarin and silibinin against experimentally induced renal carcinogenesis in male Wistar rats, it was reported that silymarin and silibinin application weakened toxicity indicators in serum, decreased lipid peroxidation, considerably strengthened renal antioxidant arsenal, as well as increased GST enzyme activity and decreased GR enzyme activity. 45 In vitro experiments showed that silibinin nanoparticles protect liver cells and reduce cellular damage. This was shown by decreased serum ALP, ALT, and AST levels.…”
Section: Discussionmentioning
confidence: 99%
“…Milk thistle accumulates essential biological elements, namely selenium and cuprum, which -together with vitamin E -stimulate the formation of antibodies and strengthen the immune system of the organism, and also activate the system of antioxidative protection (Yassin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%